Methyl jasmonate improves rubber production and quality in Lactuca Serriola - Maisa Asheri; Alireza Farokhzad; Mohammad Reza Naghavi; Raheleh Ghasemzadeh; Pejman Azadi; Meisam Zargar (Scientific Reports)
Abstract The increase in demand for natural rubber has led to the search for alternative sources. Lactuca serriola is emerging as a promising candidate, as the quality of the natural rubber it produces is comparable to that of the Pará Rubber Plant, Hevea brasiliensis. This study examines the effect of methyl jasmonate (MeJA), a known elicitor, on the expression of key rubber biosynthesis pathway genes (HMGR1, HMGS1, CPT2, and SRPP1) in the latex of L. serriola plants. The expression levels of these genes increased significantly after the foliar application of 200 and 400 µM MeJA. The highest relative expression level for HMGR1, HMGS1, CPT2 and SRPP1 was 3.74, 18.56, 11.91and 16.59 fold respectively. Furthermore, the rubber content in L. serriola showed a significant rise post-treatment compared to the control with increasing the level of MeJA (6.19%, 7.24% and 7.85% which correspond to 0, 200 and 400 µM). Gel permeation chromatography revealed an augmentation in the molecular weight of extracted natural rubber from treated plants. Samples treated with 400 µM of MeJA had the highest molecular weight (1570 kg mol−1) compared to control (1186 kg mol−1). This study has demonstrated that MeJA, through the regulation of rubber biosynthesis genes, is capable of enhancing the quality and quantity of natural rubber extracted from alternative sources, such as L. serriola.